Waterproofing barriers: settings applied in landfills - Locastro, João Karlos; Angelis, Bruno Luiz Domingos De (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
With the growth of cities and expansion in the generation of municipal solid waste are becoming increasingly common the presence of landfills. These landfills must be made with waterproof barriers (liners) able to contain leachate, thereby preventing scattering of contamination plumes. In this sense, this study aims to list the major liners found in landfills, presenting their features, in addition to exposing examples applied in landfills across the country. To this end, it conducted a literature finding the different existing liners and their respective peculiarities. With the study we observed the presence of waterproof barriers consist of: geosynthetics, sludge, active barriers, municipal solid waste, benthic geocomposite, soil cement or compacted soils. It was also found that some Brazilian cities, as the case of Belo Horizonte, use to disposal landfill waste with the presence of alternative waterproofing layers. As a whole, the liner with the highest security among the classes studied were the geosynthetic liners combined with compressed ultisols, thus presenting lower permeability.